Mental illness stigma and its impact on help-seeking behavior among residents of the Eastern Region, Saudi Arabia: A cross-sectional study - Yousif M. Elmosaad; Ziyad Alabdulqader; Mohammed Alhaddad; Mohammad Aatif; Ghazi I. Al Jowf (PLoS ONE, 2026)
Background Mental illnesses are documented as a public health concern; they are a leading cause of disability and poor quality of life among individuals. Most people with mental illness do not receive treatment due to many factors, including stigma, which significantly impacts the individual’s readiness to seek help. Methods This is a cross-sectional study design conducted among individuals 18 years of age or older who lived in Al Ahsa. The data were collected through a structured questionnaire. A total of 1085 individuals participated. Descriptive statistics, chi-square test and binary logistic regression analysis were used to investigate the association and the predictors of help-seeking behavior. Results Overall, the prevalence of mental illness-related stigma was 23.1%. There was a significant association between gender and some factors associated with mental illness stigma (p < 0.05). The proportion of individuals who might not seek help with mental illnesses due to stigma was 61.0%. Multivariate analysis indicates that the individuals who had mental illness-related stigma were more likely to avoid seeking help compared to the individuals who did not have stigma (B = 0.53, OR = 1.71, 95% CI: 1.25–2.34). The young adult group aged 30–41 years was found to be more likely to seek help (B = 0.47, OR = 1.80, 95% CI: 1.01–3.20) than the other age groups. However, gender, education, employment status, and marital status were not associated with help-seeking behavior (p > 0.05). Conclusion The study indicates that the occurrences of stigma associated with mental illness was 23.1%. Approximately two-thirds of the participants in the study avoided seeking assistance for mental issues. Our multivariate analysis confirmed that the stigma related to mental illness is significantly linked to help-seeking behavior.Specifically, it was found that young adults are more likely to seek help compared to other age groups. Participants living in rural areas were less likely to seek help. These findings have significant implications for the formulation of interventions aimed at addressing mental illness stigma and promoting help-seeking behaviors.